[Cp*RhIII] in an Ionic Liquid as a Highly Efficient and Recyclable Catalytic Medium for Regio‐ and Diastereoselective Csp3–H Carbenoid Insertion. Issue 45 (22nd November 2019) - Li, Jianglian; Zhou, Lin; Wang, Yaoling; Ma, Qiang; Lei, Yuan; Lai, Ruizhi; Luo, Yi; Hai, Li; Wu, Yong
Abstract : Reported herein is a bidentate‐assisted Csp 3 –H bond insertion using Cp*Rh III /IL as a highly efficient and recyclable catalytic medium, while showing good functional group tolerance. Notably, the application of ionic liquid not only lowered the temperature, but also enhanced the diastereoselectivity of this reaction. This work significantly expanded the scope of ionic liquids in Csp 3 –H functionalizations. Abstract : A bidentate‐assisted Csp 3 –H bond insertion using Cp*Rh III /IL as a highly efficient and recyclable catalytic medium is reported. The application of ionic liquid not only lowered the temperature, but also enhanced the diastereoselectivity of this reaction. This work significantly expanded the scope of ionic liquids in Csp 3 –H functionalizations